Development and characterization of sodium caseinate based probiotic edible film with chia mucilage as a protectant for the safe delivery of probiotics in functional bakery - Anupama Semwal; Kiran Ambatipudi; Naveen Kumar Navani (Food Hydrocolloids for Health, 2022)
The probiotic edible film is a promising method to deliver the probiotics safely to exert their health beneficial effects. However, supplementation with protectants is important for the enhanced viability of probiotics under stress conditions during storage. The present study incorporated chia mucilage in sodium caseinate-based probiotic edible film as a protectant to investigate the survival of probiotic bacteria (Limosilactobacillus fermentum NKN51 and Lactobacillus brevis NKN52) embedded in films stored at 25 °C and 4 °C. We observed significantly (p < 0.001) enhanced survival of probiotic cells in the presence of chia mucilage. The inclusion of chia mucilage in film conferred enhanced probiotics’ viability, improved flexibility, and decreased solubility due to interaction between chia mucilage polysaccharides and protein matrix. Morphological examination of embedded probiotic cells using atomic force and scanning electron microscopy showed the intact bacterial cells, proving the significance of sodium caseinate and chia mucilage. Subsequently, the probiotic edible film was assessed by coating wheat buns where the probiotics’ viability was maintained for 3 weeks at 4 °C and 2 weeks at 25 °C, indicating the effective application of developed probiotic film for delivering the probiotics on the bakery products. Our study supports the applicability of chia mucilage as a promising protectant for enhanced probiotics’ viability in edible films, which may act as a suitable probiotic carrier to deliver probiotics safely for consumption. Furthermore, our study provides the plant-based natural protectant alternative of synthetic compounds and chemicals as protectants, making it a healthier way of preparing functional bakery products.